Dilemma of law enforcement against the risk of legal error in forced confessions - Asril, Inayah Dzulhijjah (Institute Of computer Science (IOCS), 2025)
The goals of criminal law enforcement are the prevention of crime and the upkeep of justice via an open and equitable judicial system. On the other hand, mistakes in identifying criminals are a common consequence of the criminal justice system's use of coerced confessions. Not only does this occurrence undermine public confidence in the justice system, but it also breaches human rights. Victims of coerced confessions have tragic consequences; in the Sengkon and Karta instances, for instance, the individuals were convicted of crimes in which they had no role. The case highlights systemic issues with how law enforcement investigates, uses evidence, and is overseen. In order to chart the connection between coerced confessions and mistake in persona, this research employs a normative legal strategy with a descriptive-analytical methodology. Furthermore, the research evaluates the efficacy of current legislation and suggests ways to avoid future problems by using a juridical-evaluative method. Legal sources used for this study range from main sources like the Criminal Procedure Code and the Convention Against Torture to secondary sources like literature reviews and case law. The study's findings suggest that outdated regulations, outdated forensic technology, a lack of public legal education, and a lack of external control mechanisms are all necessary for the legal system to improve in order to eradicate coerced confessions. By using these measures, the public's faith in the criminal justice system may be enhanced while the likelihood of individual errors is reduced. In order to help victims of wrongfully arrested recover their dignity, the research also suggests using a restorative justice strategy.